2000
DOI: 10.1097/00005131-200006000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of the Dynamic Hip Screw With Two- and Four-Hole Side Plates

Abstract: Peak load in the failure test was not found to be statistically different between the two-hole and four-hole designs. In cyclic testing, the two-hole configuration exhibited statistically smaller fragment migration in both shear and distraction than the four-hole design (p < 0.05). The strain magnitude in the side plate was not statistically different in the cyclic or failure tests. The femurs with a greater neck angle failed by crushing of the bone in the neck. The femurs with a lesser neck angle failed due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 13 publications
0
47
0
5
Order By: Relevance
“…The type of DHS device used in both the minimally invasive surgical and conventional approaches were mainly four-hole side plates, but the choice of the length of the side plate was left to the individual surgeons. Biomechanical studies demonstrated equivalent peak load to failure results when comparing the two-and four-hole DHS plates [15]. In recent studies [13,22], stable pertrochanteric fractures (AO classification 31-A1 and 31-A2) had successful fixation with two-hole DHS.…”
Section: Discussionmentioning
confidence: 93%
“…The type of DHS device used in both the minimally invasive surgical and conventional approaches were mainly four-hole side plates, but the choice of the length of the side plate was left to the individual surgeons. Biomechanical studies demonstrated equivalent peak load to failure results when comparing the two-and four-hole DHS plates [15]. In recent studies [13,22], stable pertrochanteric fractures (AO classification 31-A1 and 31-A2) had successful fixation with two-hole DHS.…”
Section: Discussionmentioning
confidence: 93%
“…[9][10][11] As a matter of surgeon's choice we did not use a shorter plate in any case to be confident regarding postoperative mobilization of the patient. Also many of our patients had Singh's index type 3 and 2 osteoporosis in whom fixation with a two hole plate was deemed to be risky in terms of stability.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also consistent with the results of published biomechanical and clinical studies. [4][5][6][7][8][11][12] The previously reported clinical series, however, either compared the plates in the management of stable fractures specifically or had small samples of un stable fractures.…”
Section: Discussionmentioning
confidence: 99%